Adherence to optimal medical therapy and control of cardiovascular risk factors in patients after ST elevation myocardial infarction in Mexico - Villalobos-Pedroza, Montserrat; Hernandez-Pastrana, Sarai; Arias-Mendoza, Alexandra; Latapi-Ruiz Esparza, Ximena; Robles-Ledesma, Mariana; Guerrero-Ochoa, Alejandra; Milanes-Gonzalez, Nelson Antonio; Solis-Jimenez, Fabio; Sierra Gonzalez-De Cossio, Alejandro; Flores-Batres, Alejandro Pablo; Brindis-Aranda, Arielle Astrid; Rivera-Pedrote, Edgar; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: In developing countries, there is a notable scarcity of real-world data concerning adherence to optimal medical therapy (OMT) and its correlation with major cardiovascular adverse events (MACE) after ST-elevation myocardial infarction (STEMI). Our study focuses on addressing this gap by evaluating adherence to OMT and examining its influence on the risk of MACE after STEMI, as well as assessing subsequent cardiovascular risk factor control in Mexico. Methods: We conducted a prospective observational study of post-STEMI patients after hospital discharge. Adherence was assessed 683 days, (IQR:78-833), using the simplified medication adherence questionnaire (SMAQ). Patients were followed-up for four and a half years to monitor MACE (cardiovascular death, cardiogenic shock, recurrent myocardial infarction, and heart failure). Results: We included 349 patients with a mean age of 58.08 years (± 10.9), predominantly male (89.9%). Hypertension (42.4%), smoking (34.3%), type 2 diabetes mellitus (31.2%), obesity (22.92%) and dyslipidemia (21.4%) were highly prevalent. Adherence to OMT per SMAQ was 44.7%. Baseline clinical characteristics of adherent and non-adherent patients did not significantly differ. OMT prescription rates included acetylsalicylic acid 91.1%, P2Y12 inhibitors 76.5%, and high intensity statin 86.6%. While non-adherent patients had a numerically higher rate of MACE (73 vs 49 first events) there was no statistically significant difference (HR 1.30, 95% CI 0.90-1.88). Discussion: In this real-world study of patients after STEMI, we found a low adherence to OMT, a low proportion of global cardiovascular risk factor control and a numerically higher incidence of recurrent major adverse cardiovascular events in non-adherent patients. Strategies to improve adherence to OMT and risk factor control are needed.